1998
DOI: 10.1046/j.1463-5224.1998.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Tonometry in three herbivorous wildlife species

Abstract: Tonometry was performed to estimate intraocular pressure (IOP) in 12 Nubian ibexes (Capra ibex nubiana), 10 Grant zebras (Equus burchelli ) and five Arabian oryxes (Oryx leucoryx), using both applanation (Tono-Pen) and/or indentation (Schiotz) tonometers. Animals were anesthetized with a mixture of etorphine hydrochloride and acepromazine maleate. Mean (+/- SD) IOP in the ibex was 17.95 +/- 4.78 mmHg (24 eyes, indentation tonometry). In the zebra, indentation tonometry (20 eyes) yielded a mean IOP of 25.30 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 8 publications
(5 reference statements)
6
42
1
Order By: Relevance
“…The present study, along with others (22-24), does not confirm the reports that IOP significantly changes with age (7,13,28). In our literature review, except for a study on humans (37) and a study on lions (24), none of recent studies (22,23,25,30,36) has reported a significant relationship between the sex variable and IOP. The present study confirms these findings, since no significant difference was found between the mean IOPs obtained with TonoVet ® and Tono-Pen Vet ® for male and female dogs of all ages.…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study, along with others (22-24), does not confirm the reports that IOP significantly changes with age (7,13,28). In our literature review, except for a study on humans (37) and a study on lions (24), none of recent studies (22,23,25,30,36) has reported a significant relationship between the sex variable and IOP. The present study confirms these findings, since no significant difference was found between the mean IOPs obtained with TonoVet ® and Tono-Pen Vet ® for male and female dogs of all ages.…”
Section: Methodscontrasting
confidence: 99%
“…Similar results were obtained in a study on Anatolian buffaloes (28). On the other hand, in a study using applanation tonometry in Capuchin monkeys no statistically significant difference was found between IOP values of different age groups (23); similar results have also been reported in ferrets (22) and three different herbivorous wildlife species (25).…”
Section: Methodssupporting
confidence: 85%
“…Average IOP levels of several species have been reported in the literature, including hedgehog (20.1±4.0mmHg) (Ghaffari et al 2011), goat (Capra hicus) (10.8±1.7mmHg) (Broadwater et al 2007), Sanjabi sheep (9.60±2.87mmHg LE, 9.15±2.36mmHg RE) (Ghaffari et al 2011), llama (Lama glama) and alpacas (Lama pacos) 16.55±3.55mmHg (Nuhsbaum et al 2000), rhinoceros (32mmHg) , capybara (16.47±4.28 mmHg) (Montiani-Ferreira et al 2008), ferret (14.5±3.2mmHg) (Montiani-Ferreira et al 2006), zebra (29.47±3.43mmHg), Arabian oryx (11.76±3.43mmHg) (Ofri et al 1998) and broad-snouted caiman (12.9±3.2mmHg) (Oriá et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular pressure is a crucial parameter when diagnosing and managing ocular hypertension, various forms of glaucoma, and monitoring ocular diseases (Ofri et al, 1998;Biros et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The documentation of intraocular pressure for clinically normal animals is beneficial for diagnosing and monitoring an ocular disease (Ofri et al, 1998). Several methods have been described for measuring IOP in clinical and research situations, including indentation, applanation or rebound techniques (Bengtsson, 1972;Leiva et al, 2006;Jeong et al, 2007).…”
Section: Introductionmentioning
confidence: 99%